Nordic Working Life and Social Dialogue in Times of Crisis - Rolandsson, Bertil; Ilsøe, Anna (Nordic Journal of Working Life Studies, 2023)
A crisis refers to some sort of disruption of established practices, routines, or procedures occurring whenever a risk has been realized (Battistelli & Galantino 2019; Beck 1986, 2006). For social actors exposed to crisis in the labor market, this means that they will have to navigate some sort of uncertainty, trying to respond to the consequences unfolding in their surroundings as well as in their own activities (Aven & Renn 2009, p. 1). As they navigate a crisis, they will have to assess further vulnerabilities and damages for their own businesses and the variety of societal values that they adhere to, seeking out opportunities to manage both risks and prospects (Bundy et al. 2017). Doing so nevertheless is difficult and leaves social actors with a variety of tensions that they must address. Historically, researchers have linked the Nordic labor markets with strong social partners (employers’ associations, trade unions, and the state), able and willing to tackle such tensions. Due to high coverage by collective agreements and supportive welfare state arrangements, they have been able both to contribute to institutional stability and support adaption and changes (Alsos & Dølvik 2021; Andersen et al. 2014; Campbell et al. 2006; Kjellberg 2023). In the wake of, for instance, the recent COVID-19 crisis and the ongoing digital transformation of work, research as well as policy and public debates have nevertheless indicated that we may face new types of critical challenges in today’s society. It is important to point out that these challenges display a great variation. For instance, current crises often seem to be global in scale – for example, climate change, digitalization, and the coronavirus pandemic – making it difficult for national-level actors to handle the consequences on their own (Beck 2006). Also, some of the crises seem to have the character of a chock occurring at a specific point in time (e.g., a financial crisis, the pandemic), whereas others have been here for years and will last far into the future (e.g., climate change), although they might change gears on the way and interact with other types of crises (Björck 2016; Enggaard et al. 2023). In addition, the nature of these challenges has to do with the strategic choices of the social partners, and whether they, as actors in the labor market, perceive the crisis as controllable, and perhaps something that could be exploited to strengthen their position in the Nordic society or not (Boin & ‘t Hart 2022; Boin et al. 2008). These are all different conditions that play a role for Nordic social partners’ ability and willingness to act. We may ask ourselves in what way today’s crises and linked developments affect the Nordic labor markets and the Nordic social dialogue. Are the institutional foundations for adaption to various crises still able to provide means and measures to address future challenges in the Nordic countries? In this special issue, we address these questions, contributing to research on the future of Nordic working life during times of uncertainties by exploring the meaning and the impact of different types of crises and responses. The coronavirus pandemic constitutes a prominent crisis theme throughout this special issue, but the articles also address issues often framed as labor market crises due to digitalization and the emergence of platform work. The articles display a great diversity of both theoretical assumptions and empirical materials. The texts draw on different types of historical, comparative, quantitative, or qualitative data, revealing that the way we approach or conceptualize what we mean by a crisis is not self-evident. The articles are sensitive to the contextual differences, and the fact that involved actors and organizations in the Nordic labor markets face a variety of different risks and have different views of the crises they encounter. Authors of the articles thereby also recognize that most of the actors involved in managing the different crises in the Nordic labor markets differ when it comes to the amount of risk they are willing to take as they strive with different aims (Battistelli & Galantino 2019)